Pengaruh propolis terhadap profil lipid plasma tikus model hiperkolesterolemia - Krisnansari Diah; Ariadne Tiara Hapsari; Evy Sulistyoningrum; Agus Prastowo (Jurnal Gizi Klinik Indonesia, 2012)
Background: Nowadays, cardiovascular disease caused by hypercholesterolemia has become the main cause of death. Propolis has been used widely to reduce plasma cholesterol levels.Objective: The aims of this research was to study the effect of propolis on lipid profile of hypercholesterolemic Sprague Dawley rats.Method: This was an experimental study with pre-post test. Twenty four (24) male Sprague Dawley rats aged 12-16 week old, weighing 125-200 g were allocated into 4 groups. Group I received standard meal + aquadest-gavage; group II received high cholesterol meal + PTU 0,01 + aquadest gavage; group III received high cholesterol meal + PTU 0,01 + 0,027 g propolis gavage; group IV received high cholesterol meal + PTU 0,01 + 0,054 g propolis gavage. Total cholesterol, triglycerides, HDL cholesterol and LDL cholesterol levels before and after treatment were measured. The data were then analyzed with One Way Anova.Results: The study showed that there were no significant differences in changes of body weight. There were significant differences in total cholesterol levels between all groups of treatment. Triglyceride levels were significantly different among all groups, except between group I and IV. Furthermore, the HDL cholesterol levels of group I vs III and group I vs IV were significantly different. However, there were no differences found in LDL cholesterol levels among all groups of treatment.Conclusion: Provision of 0,027 g and 0,054 g propolis improve lipid profile (total cholesterol, triglyceride and HDL cholesterol levels) of hypercholesterolemic rats.